Meningkatkan Kompetensi Guru dalam Menyusun Silabus dan RPP Melalui Supervisi Akademik Berkelanjutan di SMP Negeri 2 Sabang - Faridah Faridah (Tadabbur: Jurnal Peradaban Islam, 2019)
The study entitled "Improving teacher competence in preparing syllabus and lesson plans through ongoing academic supervision in SMP (Public Middle Schools) Negeri 2 Sabang" raised the issue of whether through continuous academic supervision it can improve teacher competence in preparing syllabi and lesson plans. This study aims to improve the competence of teachers in Sabang 2 Public Middle School in preparing syllabus and lesson plans. The subjects of this study were teachers of Sabang 2 Public Middle School in the 2016/2017 academic year, totaling 13 teachers, consisting of 10 PNS teachers and 3 non PNS teachers. The method used is the school action research method. Data collection is done by test and observation techniques. The study was conducted in 2 cycles. In the first cycle 31% of teachers obtained the appropriate syllabus and lesson plan and were considered good and in cycle 2 there were 100% of teachers who had syllabus and lesson plans that were appropriate and considered good. The conclusion of this research is that through ongoing academic supervision scientifically proven to improve teacher competence in preparing syllabus and lesson plans.